OP0095 Therapeutic efficacy of multiple intravenous infusions of anti-tumour necrosis factor-alfa monoclonal antibody (infliximab) in persistently active refractory juvenile idiopathic (chronic) arthritis. an one year open prospective pilot study. (1st June 2001) - Gerloni, V; Pontikaki, I; Desiati, F; Lupi, E; Gattinara, M; Fantini, F
Abstract : Background: Objectives: An open prospective trial was carried out in a young population affected by severe, refractory, polyarthritic JIA to evaluate the efficacy and safety of Infliximab (Remicade). Methods: We enrolled 17 females, median age at the start of the therapy 22.9 yrs (8–33), median onset age 3 yrs (1–16), median disease duration 15.6 yrs (5–31). All patients had been previously treated with more than one DMARD (median number 3.5/patient, as mono or combined therapy). All patients had still active disease: number of active joints (median 5.5), ESR (median 59.5 mm/hr), CRP (median 4.7 mg/dl), physician global evaluation (median VAS 45.5), HAQ (median D. I. 1.13). 14 patients were still on corticosteroids (median 0.11 mg/kg). All patients discontinued any other DMARD aside from s.c. MTX (median weekly dose 15 mg, range 5–25) and continued with previous NSAIDs and corticosteroids. Infliximab was administrated as a single infusion of 3 mg/kg at time 0 and at weeks 2, 6, 14, 22, 30. Results: Until now all 17 pts have received the first 2 infusions, 15 pts 3 infusions, 9 pts 6 infusions, 8 pts 7 infusions, 2 pts 8 infusions and 1 pt 10 infusions. One patient withdrew because of a severe adverse event (hypersensitivity reaction at the third infusion). Since the 1st infusion, all 17 patients achieved a very good response (50% reduction in number of active joints, ESR, CRP, VAS). A statistically significant improvement of the following parameters was observed at the 6th infusion assessment (evaluation on 9 patients who completed 30 weeks = 5 months of therapy): the median number of active joints decreased from 5 to 0; ESR decreased from a median of 65 to 23 mm/hr and CRP decreased from a median of 4.6 to 0.4 mg/dl; the median score of the VAS (physician global evaluation) decreased from a 65 to 2. Furthermore after 6 months of therapy we observed a trend to improvement in all scales of SF36 (assessment of the quality of life). An eleven-year-old girl with chronic active uveitis showed a great improvement of the visus. Conclusion: These data suggest that Infliximab can significantly and promptly reduce disease activity and improve the quality of life of patients affected by persistently active and refractory JIA. However more data are needed to evaluate its efficacy and safety as a long-term therapy.